HALAL CHARACTERISTICS OF SMALL AND MEDIUM MICRO BUSINESS PRODUCTS (MSMEs) IN PATEMON VILLAG KREJENGAN SUB-DISTRICT PROBOLINGGO DISTRICT - Susanti, Dyah Ochtorina (Warmadewa Press, 2021)
This research is motivated by the fact that there are still products of Micro, Small and Medium Enterprises (MSMEs) in Patemon Village, Krejengan District, Probolinggo Regency, which do not yet have a halal certificate, because the product does not qualify the halal criteria and the public does not understand about the characteristics of halal. This study aims to analyze and provide an understanding about the characteristics of halal, especially on MSME products in Patemon Village, Krejengan District, Probolinggo Regency. The results of the study using the normative legal research with the statute approach, conceptual approach, and comparative approach is that the halal characteristics of MSME products in Patemon Village can be seen from 2 (two) aspects, namely the material and the process of making it or the event to get it. At the end of this study, the researcher also gave advice to MSME product producers in Patemon Village to immediately take care of their halal product certification and to the government to disseminate information to the public regarding about characteristics of halal on MSME products.